2004
DOI: 10.1002/dc.20010
|View full text |Cite
|
Sign up to set email alerts
|

Mixed follicular‐medullary thyroid carcinoma: A case report

Abstract: We report on a 35-yr-old woman presenting with a single thyroid nodule. Fine-needle aspiration (FNA) of the nodule was reported to contain both follicular and parafollicular cells. The biphasic nature of the tumor was highlighted on immunohistochemical investigation of the cellblock. Positive staining for thyroglobulin was limited to the follicular structures and the dense areas stained positive for calcitonin. The serum calcitonin level was highly elevated. Surgery was recommended because of suspected maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…As such, the terminology used to describe these tumors is not uniform. For thyroid carcinomas of merged histological type, the designations in the literature include ''mixed thyroid carcinoma'' [2], ''simultaneous thyroid cancer'' [3], ''synchronous occurrence of thyroid carcinoma'' [5], ''compound carcinoma of the thyroid'' [19], ''stem cell carcinoma'' [14], ''composite carcinoma of the thyroid'' [16], and ''differentiated thyroid carcinoma, intermediate type'' [33], to name a few. Apel et al [16] suggested that such multifocal lesions, with each lesion containing only one histological type of thyroid carcinoma, should be termed as ''composite'', while a single lesion containing a variety of histological types of thyroid cancer should be referred to as ''mixed'' in order to differentiate the two.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the terminology used to describe these tumors is not uniform. For thyroid carcinomas of merged histological type, the designations in the literature include ''mixed thyroid carcinoma'' [2], ''simultaneous thyroid cancer'' [3], ''synchronous occurrence of thyroid carcinoma'' [5], ''compound carcinoma of the thyroid'' [19], ''stem cell carcinoma'' [14], ''composite carcinoma of the thyroid'' [16], and ''differentiated thyroid carcinoma, intermediate type'' [33], to name a few. Apel et al [16] suggested that such multifocal lesions, with each lesion containing only one histological type of thyroid carcinoma, should be termed as ''composite'', while a single lesion containing a variety of histological types of thyroid cancer should be referred to as ''mixed'' in order to differentiate the two.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the cases reported in the literature are carcinomas, and most of those consist of two merged types, i.e., papillary and follicular carcinoma of a generally mixed character [1]. In the literature, medullary merged follicular carcinomas are represented by only about 30 cases [2] and medullary merged papillary carcinoma by about 20 [3]. Three merged histological types are even rarer and only 4 cases exist in the literature [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The standard diagnostic criteria for MCT are well established from a few large series evaluating cytomorphological features 6–15 . However, a systematic study evaluating the cytology of medullary carcinoma with emphasis on variants and their distinction from the usual types of medullary carcinoma is not available, being restricted to a few case reports 16–25 . The present study, based on 78 aspirates, highlights the majority of medullary carcinoma variants and their cytological findings.…”
Section: Introductionmentioning
confidence: 95%
“…The differentiated thyroid cancers represent about 80% of all thyroid cancers [2], with a good prognosis [4, 5], while medullary, respectively, anaplastic forms, with considerable lower incidences [1, 69], have an aggressive evolution, frequently very severe and fast. The mixed forms are very rare and considered to be of different cell origins, with specific clinical behaviours [1015]. …”
Section: Introductionmentioning
confidence: 99%